Systematic analysis and case series of the diagnosis and management of trichilemmal carcinoma - Sun, Jiachen; Zhang, Lihua; Xiao, Minglu; Li, Shiyi; Chen, Runkai; Li, Ying; Yang, Yuguang (Frontiers in Oncology, 2023)
Background Trichilemmal carcinoma (TLC) is a rare malignant cutaneous adnexal neoplasm, with no relatively comprehensive research. Objective The aim of this study is to perform an updated statistical analysis so as to better understand TLC’s epidemiology, clinical features, diagnosis, and treatment. Methods The diagnosis and treatment of three TLC cases in our department were summarized. Then, all TLC cases published in the literature were retrieved for a comprehensive analysis, followed by the analysis of global trends and regional distribution, demographic characteristics, clinical features, pathogenesis, histopathological features, and treatment and prognosis of TLC. Results Of the 231 cases, the incidence of TLC has shown an upward trend recently, especially in China, in Asia. The susceptible population is men aged 60–80 and women over 80, and the most prone location is head and neck. The phenotype of TLC is not always typical and may be misdiagnosed because of the coexistence of other diseases. There is a linear relationship between the diameter and its duration or thickness. UV, locally present skin lesions, trauma, scarring, organ transplantation, and genetic disorders may trigger the occurrence of TLC. Periodic acid–Schiff staining and CD34, but not Epithelial Membrane Antigen (EMA), were helpful in the diagnosis of TLC. Although effective, surgical excision and Mohs micrographic surgery need further improvement to reduce recurrence of TLC. Carcinoma history is an independent risk factor for TLC recurrence. Limitations The limitation of this study is the lack of randomized controlled trial on TLC treatment and recurrence. Conclusion TLC has the possibility of invasive growth and recurrence, especially in patients with longer duration and carcinoma history.